1993
DOI: 10.1016/0928-8244(93)90051-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dimethyl dioctadecyl ammonium bromide, Freund's complete adjuvant and mineral oil for induction of humoral antibodies, cellular immunity and resistance to Newcastle disease virus in chickens

Abstract: Dimethyl dioctadecyl ammonium bromide (DDA), a lipophilic quaternary amine, was evaluated in adult chickens for potentiation of immunological responses to subcutaneously administered inactivated Newcastle disease virus (NDV) vaccines. DDA enhanced humoral and cell-mediated immune (CMI) responses to levels which were significantly higher than those induced by the vaccine alone The haemagglutination inhibition antibody titers induced by DDA were slightly lower than those induced by mineral oil although neutraliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…We have tested different incubation timings in the cell proliferation assay (2, 3, 4 and 7 days) and no significant proliferation was observed after ex vivo NDV stimulation (data not shown). NDV-specific proliferative responses of PBLs from NDV-vaccinated chickens, using an inactivated NDV as recall antigen, have been reported (Katz et al, 1993;Reynolds & Maraqa, 2000b). These different results might be explained by differences in the vaccination schedule.…”
Section: Discussionmentioning
confidence: 85%
“…We have tested different incubation timings in the cell proliferation assay (2, 3, 4 and 7 days) and no significant proliferation was observed after ex vivo NDV stimulation (data not shown). NDV-specific proliferative responses of PBLs from NDV-vaccinated chickens, using an inactivated NDV as recall antigen, have been reported (Katz et al, 1993;Reynolds & Maraqa, 2000b). These different results might be explained by differences in the vaccination schedule.…”
Section: Discussionmentioning
confidence: 85%
“…Although mineral oil emulsions are used in a wide range of food animals, their undesirable side effects, such as deterioration in the meat quality at the injection sites and the risk of mineral oil residues in the meat from these animals, highlights the need for new adjuvants [13]. This study evaluated DDA, CpG-ODN and ChIFN-γ, which have been reported to be immunomodulators against various infectious diseases in many animal models [7,14,16,22,42], as adjuvants for pcDNA-VP243 vaccine against IBDV [17]. …”
Section: Discussionmentioning
confidence: 99%
“…Synthetic CpG-ODN (10 µg/bird) along with the DNA vaccine was injected. A DDA (Sigma, USA) solution (2 mg/bird) was prepared as described previously [16] and also injected along with the DNA vaccine.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the oil phase, different adjuvants can be added to inactivated vaccine formulations to increase immunogenicity (62–65). Such adjuvants can include chemicals, microbial components, or proteins that increase the overall immune responses to vaccine antigens (66).…”
Section: Current Status Experimental and Commercial Ai Vaccines For Tmentioning
confidence: 99%